Mental Health Care Financing in the Process of Change Challenges and Approaches for Austria - Zechmeister, Ingrid (Forschungsergebnisse der Wirtschaftsuniversitaet Wien, 2018)
While mental health care has undergone substantial reforms, little attention has been paid to financing issues. This book addresses this shortcoming and brings more transparency into the complex relationship between mental health care reform, service provision and financing. Additionally, it provides rich information about the characteristics of mental health care financing in Western Europe. The author analyses the recent mental health care reform discourse against the backdrop of broader political economic developments and demonstrates the role of financing arrangements herein. The book vividly shows how financing is related to specific effects for service users and their relatives in the process of change. In the final part practitioners, planers and policy makers find useful guidelines for developing alternative financing approaches including support to improve understanding of financing issues amongst those involved in mental health care.